Can a surgical treatment centre reduce waiting lists? Results of a natural experiment. Issue 5 (October 1993) - Harvey, I; Webb, M; Dowse, J
Abstract : STUDY OBJECTIVE–To determine the effectiveness of the Welsh general surgery (hernia and varicose veins) treatment centre established as part of the NHS reforms, in terms of its impact upon throughput and waiting lists. DESIGN–This was a natural experiment with two control groups–other surgical specialties without treatment centre provision, and general surgery in districts that made only minor use of the facility. SETTING–General Surgery Treatment Centre, Bridgend General Hospital. SUBJECTS–All patients referred between 1 April 1990 and 31 March 1991. MEASUREMENTS AND MAIN RESULTS–Main outcome measures were throughput for hernia and varicose vein operations, non-urgent inpatient waiting list lengths before and after the opening of the centre and patient satisfaction. Altogether 1097 patients were referred during the year. Of these, 160 (15%) did not attend outpatient assessment and 79 (8%) of those who did were unsuitable for surgery. A total of 750 operations were performed–448 (60%) for varicose veins and 261 (35%) hernia repairs. Among the residents of the four main districts using the centre (with valid data available), there was a significant increase in the total number of varicose vein operations performed but no significant increase in hernia repairs. In the six districts that made major use of the centre, general surgery waiting lists for non-urgent cases fell significantly (p < 0.0001) while those for ear, nose, and throat showed no significant change and gynaecology lists lengthened significantly (p < 0.0001). In the three districts that made minor use of the centre general surgery waiting lists showed no change. CONCLUSIONS–Relations between inputs and waiting lists are often unpredictable, but after controlling for confounding trends there is sound evidence that such a centre provides an acceptable and effective approach to the waiting list problem.